Nutritional and herbal interventions for polycystic ovary syndrome (PCOS): a comprehensive review of dietary approaches, macronutrient impact, and herbal medicine in management - Aya A. Muhammed Saeed; Sobia Noreen; Farhang H. Awlqadr; Muhammad Irshad Farooq; Maria Qadeer; Nadia Rai; Halgurd Ali Farag; Mohammed N. Saeed (Journal of Health, Population and Nutrition)
Abstract Polycystic Ovary Syndrome (PCOS) is a common health condition related to a woman’s hormonal problems. Hormonal imbalance, metabolic disorders, and an increased insulin level mainly characterize the ailment. This detailed review focuses on dietary strategies, macromolecules, macromolecules, and herbal interventions that exception-ally work in PCOS treatment. Research has shown that Mediterranean, low-glycemic index, and ketogenic diets that are modified with individuals in mind are the best ways to resolve insulin resistance, obesity, and lack of ovulation. The other nutrients shown to affect glucose metabolism and play a role in hormone regulation are the macromolecules, such as increased protein and reduced refined carbs. Among the different micronutrients, vitamin D, omega-3 fatty acids, and inositol were shown to be the most vital supplements in the treatment of PCOS-induced oxidative damage, hyperandrogenism, and infertility. Not to mention, cinnamon, curcumin, sage, fennel, and traditional Chinese herbal medicine are among some of the herbal remedies that so far show good potential to be the perfect complementary therapy tools as they create better glycemic control, inflammation reduction, and menstrual cycle regularization. Even though the findings are promising, the current supply of clinical trials for standardizing these nutritional and herbal protocols is lacking. Overall, this report stresses the fact that a customized, holistic diet regime is the best treatment for women with PCOS to make them feel well and live a long and healthy life.